Authority and trust in US culture and society: interdisciplinary approaches and perspectives - Leypoldt, Günter; Berg, Manfred (American culture studies, 2021)
In the past two decades, a discourse of crisis has emerged about the democratic institutions and political culture of the US: many structures of authority which people had more or less taken for granted are facing a massive public loss of trust. This volume takes an interdisciplinary and historical look at the transformations of authority and trust in the United States. The contributors examine government institutions, political parties, urban neighborhoods, scientific experts, international leadership, religious communities, and literary production. Exploring the nexus between authority and trust is crucial to understand the loss of legitimacy experienced by political, social, and cultural institutions not only in the United States but in Western democracies at large
Literaturangaben
Keywords: United States -- Politics and government; États-Unis - Politique et gouvernement; United States; Aufsatzsammlung; Geschichte 1800-2020; Vertrauen; Legitimität; Autorität; USA